The African correspondence of Sir Joseph Banks, 1767-1820. - Banks, Joseph, 1743-1820, author. Link
1 online resource
Keywords: "This edition brings together in three fully edited volumes the correspondence and associated papers of Sir Joseph Banks regarding European and especially British exploration of Africa from 1767-1820, for the first time publishing this globally scattered material in one place, thereby revolutionizing its availability and understanding of the activities of a key figure who helped organize and publish a series of missions to penetrate the African interior, mainly from West Africa and by crossing the Sahara from Cairo and Tripoli. Banks was a founder in 1788 of the African Association, which mounted many of these missions, including those of Mungo Park to explore the River Niger, and J.L. Burkhardt exploring Syria, Arabia and Egypt. At the time, little was known about the African interior, its peoples, kingdoms and resources, and the aim of the African Association under Banks was to discover what lay there, to make contact with and study its societies, to map them and their lands and help establish trading links. Banks also maintained a lively correspondence with British diplomatic representatives in North Africa, such as James Mario Matra at Tangier and Henry Salt in Cairo, who were a rich source of news. Moreover, as unofficial director of the royal gardens at Kew he sent pioneering plant collectors to gather plants in South Africa, vastly boosting knowledge of this region's important flora. At home, he corresponded with politicians, government officials, entrepreneurs, navigators, naturalists and campaigners like William Wilberforce about a great range of issues surrounding Africa. This work is multi-disciplinary and will stand alongside existing series of Banks's correspondence published by Neil Chambers (Scientific Correspondence, 2007; Indian and Pacific Correspondence, 2007-14). It will appeal to scholars of African history in the Early Modern Period, to those studying exploration and collecting as well as those interested in natural history, the history of science, geography, cartography and the Enlightenment. An Introduction, detailed Calendar of Correspondents, Timelines for each volume and a comprehensive Index supplement the footnotes to nearly 800 documents included in this fascinating and comprehensive new series"--